RESPONSE - Green, Jay D. (Fides et historia, 2017)
The author offers his response to comments on his book "Christian Historiography: Five Rival Versions." He says that his book's basic proposition highlights that faith matter to historical study and that its burden is to invite professional skeptics to re-examine and revisit Christian historiography.